Zróżnicowanie potomstw z wolnego zapylenia świerka pospolitego (Picea abies (L.) Karst.) po 5 latach wzrostu na powierzchni testującej w Tomaszowie Lubelskim - Wojda, Tomasz; Kowalczyk, Jan; Mohytych, Vasyl (Leśne Prace Badawcze, 2025)
Norway spruce (Picea abies (L.) Karst.) is gradually disappearing from many stands due to limited water availability and rising temperatures. In addition, obtaining seeds from seed stands encounters specific difficulties. For this reason, in recent years, selection and breeding activities have focused on identifying the properties of individual genotypes and establishing seed plantations from selected individuals. Spruce seeds are currently obtained from such plantations that, as many original populations have been degraded or have ceased to exist. The aim of forest tree progeny testing is to determine the genetic value and breeding quality of the components of forest basic material used in forest management. The genetic value of an individual differs from its phenotypic value. When assessing genotype traits, the interrelationships between offspring and parent individuals in terms of trait transmission should be examined, and the best way to determine the genetic value of parents is to breed their offspring. Testing forest basic material therefore involves setting up experiments that compare the growth of the tested origins or individuals under different environmental conditions. The research was conducted on a test plot located in south-eastern Poland. It contained a total of 123 Norway spruce families belonging to 11 provenances (Fig. 1). The aim of the study was to assess the variability of Norway spruce families and provenances in terms of adaptive and growth traits. The survival rate in the first, second, and fifth years of tree growth was determined, and the height of surviving trees after 5 years was measured. The average overall survival rate of trees after the first growing season was 93.01% (Tab. 1) and varied between provenances from 90.83% (Św50 Janów Lubelski) to 96.76% (Św50 Gościeradów). The average overall height of Norway spruce trees after five years of growth on the test area (Tab. 1) was 169.9 cm. The tallest trees belonged to the Kolonowskie II generation provenance (194.8 cm), while the shortest ones belonged to Św50 Gościeradów (154.7 cm). The family with the lowest average tree height (126.4 cm) was 8525 from the provenance Św50 Tomaszów, while the family with the highest average height (228.0 cm) was G4226 from the provenance Kolonowskie II generation. The three tallest individuals (364, 350, 349 cm) in the entire test area came from the G4226 family, provenance Kolonowskie II generation. We found that tree survival in the first and second years after planting, as well as after five years, was not significantly dependent on genotype. In contrast, tree height and growth rate showed strong genetic determination. The families differed significantly in height, while variability in survival did not reach statistical significance and was characterised by very low individual heritability. This indicates that environmental factors mainly determined the young tree mortality, with family affiliation being of secondary importance. After five years of growth, the genetic component accounted for less than 5% of the total phenotypic variability in the survival trait. The occurrence of clear differentiation and a relatively high heritability value (h² > 0.5) indicate a real possibility of effective selection and breeding progress for growth traits. The effectiveness of phenotypic selection was also demonstrated by the better growth of offspring from populations with documented potential, such as Kolonowskie II generation, spruce from the Suchedniów Forest District (offspring of IBL seed plantation No. 200 in the Pińczów Forest District), and spruce from Zwierzyniec Lubelski.